Size Miniaturized Coaxial Probe Fed Antenna for Multiband Applications - Heydarpanah, B.; Ghobadi, C.; Nourinia, J.; Beigi, P.; Majidzadeh, M. (Advanced Electromagnetics, 2020)
A novel coaxial cable-fed antenna with a combination of L-shaped elements is proposed for multiband applications. The obtained resonances at different frequency bands are realized by adding L-shaped strips with different lengths to the antenna geometry. The antenna is printed on a low-priced FR-4 substrate with overall size of 14×14×1.6 mm3. Experimental results indicate the coverage of 1.32, 1.80, 2.34, 3.30, 3.66, 4.26, 5.28, 7.68, 8.1, 9.72 and 10.38 GHz, compatible with L-band, WLAN, WiMAX, C-band, ITU 8 GHz, and X-band. Suitable radiation properties, multiband functionality, desirable gain values and agreement of simulated and measured results confirm the suitability of the proposed structure for multiband communication applications.